Mastery motivation: A way of understanding therapy outcomes for children with unilateral cerebral palsy - Miller, L.; Ziviani, J.; Ware, R.; Boyd, Roslyn (2015)
© 2014 Informa UK Ltd. All rights reserved: reproduction in whole or part not permitted. Purpose: To investigate the impact of mastery motivation on occupational performance outcomes immediately following upper limb (UL) training and 6 months post-intervention for school-aged children with unilateral cerebral palsy. Method: This prediction study was a post-hoc analysis of a matched pairs randomized comparison trial (COMBiT Trial Registration: ACTRN12613000181707). The Canadian Occupational Performance Measure (COPM) was administered at baseline, 13 and 26 weeks post-intervention. Parents completed the Dimensions of Mastery Questionnaire (DMQ), Parenting Scale and a demographic questionnaire. Children's UL capacity and performance was assessed using the Melbourne Assessment of Unilateral UL Function and assisting hand assessment (AHA). Regression models were fitted using generalized estimating equations to baseline, 13 and 26 week measurements. Results: Forty-six children (7.78 years SD 2.27 years, 31 males, Manual Ability Classification System I=23, II=23) participated. Higher levels of bimanual performance (AHA: ß=0.03, p<0.001), greater object-oriented persistence (DMQ: ß=0.31, p=0.05), and treatment group allocation (Standard Care: ß=0.24, p=0.01) were positively associated with COPM performance scores post-intervention. Conclusions: Children's bimanual performance and persistence with object-oriented tasks significantly impact occupational performance outcomes following UL training. Predetermining children's mastery motivation along with bimanual ability may assist in tailoring of intervention strategies and models of service delivery to improve effectiveness.Implications for RehabilitationChildren's object persistence and bimanual performance both impact upper limb training outcomesWorking with children's motivational predispositions may optimize engagement and therapy outcomes.Supporting positive parenting styles may enhance a child's mastery motivation and persistence with difficult tasks.